The Problem of Evil in Ibn Sina’s Philosophy - Masoumeh RajabNezhadian ,Abdullah HosseiniEskandian (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The problem of evil is one of the cases that has occupied the human mind for a long time and has caused thinkers to think about it.Ibn Sina, who is one of the best Islamic philosophers, explains the problem of evil and considers evil as a non-existent thing that lacks nature and essence, and on the other hand, the problem of evil can not challenge the goodness of the world of creation or divine attributes.Familiarity with Ibn Sina's thoughts and his solutions for solving the problem of evil is something that can acquaint us with his thoughts on this subject.In this article, with a descriptive-analytical method and using reliable references, the nature of evil, types of evil, as well as solutions to the problem of evil in Ibn Sina's book are discussed.Ibn Sina considers evil to be inherently non-existent, which, since it has no essence, cannot deny the existence of God.